Pharmacotherapeutic Options for Managing Neuropathic Pain: A Systematic Review and Meta-Analysis - Giulia Di Stefano; Andrea Di Lionardo; Giuseppe Di Pietro; Giorgio Cruccu; Andrea Truini (Pain Research and Management)
Despite an increasing number of available therapies, the treatment of neuropathic pain remains a major issue. Systematic reviews and meta-analyses indicate that only a minority of patients with neuropathic pain have an adequate response to pharmacological treatment and that most drugs have dose-limiting side effects. We conducted a systematic review and meta-analysis of randomised controlled trials published in the last five years. We searched for relevant papers within PubMed, EMBASE, the Cochrane Database of Systematic Reviews, and the Clinical Trials database (ClinicalTrials.gov). Two authors independently selected studies for inclusion, data extraction, and bias assessment. We identified 39 randomised controlled trials and included 16 in the meta-analysis. Trial outcomes were generally modest even for first-line drugs such as tricyclic antidepressants, serotonin-noradrenaline reuptake inhibitors, and gabapentinoids. Many drugs acting on new pain targets are currently under development. Clinical data are currently available for sodium channel isoform-specific antagonists, anti-nerve growth factor molecules, and fatty acid amide hydrolase inhibitors.